Binding of Natural Peptide Ligands to the Neuropeptide Y5 Receptor. (16th December 2021) - Rudolf, Sarina; Kaempf, Kerstin; Vu, Oanh; Meiler, Jens; Beck‐Sickinger, Annette G.; Coin, Irene
Abstract: The binding mode of natural peptide ligands to the Y5 G protein‐coupled receptor (Y5 R), an attractive therapeutic target for the treatment of obesity, is largely unknown. Here, we apply complementary biochemical and computational approaches, including scanning of the receptor surface with a genetically encoded crosslinker, Ala‐scanning of the ligand and double‐cycle mutagenesis, to map interactions in the ligand‐receptor interface and build a structural model of the NPY‐Y5 R complex guided by the experimental data. In the model, the carboxyl (C)‐terminus of bound NPY is placed close to the extracellular loop (ECL) 3, whereas the characteristic α‐helical segment of the ligand drapes over ECL1 and is tethered towards ECL2 by a hydrophobic cluster. We further show that the other two natural ligands of Y5 R, peptide YY (PYY) and pancreatic polypeptide (PP) dock to the receptor in a similar pose. Abstract : Complementary biochemical methods and molecular modeling reveal how NPY and its natural analogues bind to the Y5 GPCR, filling in the gap in the knowledge of the Y multiligand/multireceptor system. This provides the first base for the rational design of selective Y5 R ligands with therapeutic potential.